The Impact of COVID-19 in Europe: An Overview of the Pandemic's Challenges and Responses - Henry Gaubert (Global Writing Academica Researching and Publishing, 2023)
The COVID-19 pandemic has emerged as one of the most significant global health crises in recent history, affecting nearly every corner of the world, including Europe. This article aims to provide a comprehensive overview of the impact of COVID-19 in Europe, focusing on the challenges faced by the region and the responses adopted by various countries to combat the spread of the virus. By examining the epidemiological trends, healthcare infrastructure, socio-economic implications, and public health strategies, this study aims to shed light on the lessons learned from the pandemic and the way forward for Europe's health systems.